Dermapen Treatments for Healing Pockmarked Skin in Male Wistar Rats (Rattus norvegicus): A Study Comparing Platelet-Rich Plasma with Salmon DNA Serum - Chiuman, Linda; Hestina; Ongko, Nicolas Xavier; Tarigan, Setia Budi (Postgraduate, University of Mataram, 2023)
Skin issues like deep acne scars (pockmarks) are routinely addressed. Dermaroller and Dermapen face skin care help cure this issue. Researchers believe plasma from platelets (PRP) and salmon DNA serum dermapens work similarly on pockmarked skin. White Wistar mice were tested to confirm this suspicion. This is a lab study or an experiment. The study employed a post-test only with a control group design on 16 white Wistar rats (Rattus norvegicus) divided into two groups of eight rats each: Group I received platelet plasma dermapen (PRP) and Group II received salmon DNA serum dermapen. The collected data was tested for normalcy using SPSS. The data normality test showed a significance value of 0.20 > 0.05, indicating normal distribution. The homogeneity test is 0.224. The significant probability value is greater than 0.05, indicating that the PRP dermapen group and the salmon serum DNA dermapen group have similar variances. The t-test rejects H0 or shows a significant difference in wound healing between groups if the significance value is 0.00 or less than 0.05. The study found that PRP and salmon DNA serum promote wound healing. Healing was faster in the PRP than in the salmon DNA serum group. This is possible because PRP includes bioactive molecules that act as tissue growth factors to enhance proliferation. PRP contains various growth factors that aid wound healing.